A comparative study on 4-(4-(3-mesityl-3-methylcyclobutyl)thiazole-2-yl)-1-thia-4-azaspiro[4.5]decan-3-one: Experimental and density functional methods - Sen, Fatih; Ekici, Oner; Dincer, Muharrem; Cukurovali, Alaaddin (Elsevier, 2015)
In the present study, combined experimental and computational study on molecular structure and spectroscopic assignments of title compound has been reported. The crystal was synthesized and its molecular structure brought to light by X-ray single crystal structure determination method. The spectroscopic properties of the compound were examined by FT-IR and NMR (H-1 and C-13) techniques. FT-IR spectrum in solid state was observed in the region 4000-400 cm(-1). The H-1 and C-13 NMR spectra were recorded in Acetone-d(6) and CDCI3 solvents. The molecular geometry were those obtained from the X-ray structure determination was optimized using Density Functional Theory (DFF/B3LYP) method with the 6-31G(d, p) and 6-31+G(d, p) basis sets in ground state. From the optimized geometry of the molecule, geometric parameters (bond lengths, bond angles and torsion angles), vibrational assignments and chemical shifts of the title compound have been calculated theoretically and compared with the experimental data. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cyclobutane; Thiazole; X-ray structure; Density Functional Theory (DFT); IR and NMR spectroscopies